Profile of Psoriasis Vulgaris in Waled General Hospital, Cirebon, Indonesia: A Retrospective Study (January 2020-December 2023) - Fadhlan Adiguna Putra; Frista Martha Rahayu; Maya Wahdini (GHMJ (Global Health Management Journal))
Background: Psoriasis is a chronic skin disease that significantly impacts the quality of life. In Indonesia, it affects 2.5% of the population, with increasing cases observed in major hospitals. This study aimed to profile psoriasis vulgaris at Waled General Hospital, Cirebon, from January 2020 to December 2023.